Increased presence of capillaries next to remodeling sites in adult human cancellous bone. (15th February 2013) - Kristensen, Helene Bjoerg; Andersen, Thomas Levin; Marcussen, Niels; Rolighed, Lars; Delaisse, Jean‐Marie
Abstract: Vascularization is a prerequisite for osteogenesis in a number of situations, including bone development, fracture healing, and cortical bone remodeling. It is unknown whether a similar link exists between cancellous bone remodeling and vascularization. Here, we show an association between remodeling sites, capillaries, proliferative cells, and putative osteoblast progenitors. Iliac crest biopsies from normal human individuals were subjected to histomorphometry and immunohistochemistry to identify the respective positions of bone remodeling sites, CD34‐positive capillaries, smooth muscle actin (SMA)‐positive putative osteoblast progenitors, including pericytes, Ki67‐positive proliferative cells, and bone remodeling compartment (BRC) canopies. The BRC canopy is a recently described structure separating remodeling sites from the bone marrow, consisting of CD56‐positive osteoblasts at an early differentiation stage. We found that bone remodeling sites were associated with a significantly increased presence of capillaries, putative osteoblast progenitors, and proliferative cells in a region within 50 µm of the bone or the canopy surface. The increases were the highest above eroded surfaces and at the level of the light‐microscopically assessed contact of these three entities with the bone or canopy surfaces. Between 51 and 100 µm, their densities leveled to that found above quiescent surfaces. Electron microscopy asserted the close proximity between BRC canopies and capillaries lined by pericytes. Furthermore, the BRC canopy cells were found to express SMA. These ordered distributions support the existence of an osteogenic‐vascular interface in adult human cancellous bone. The organization of this interface fits the current knowledge on the mode of action of vasculature on osteogenesis, and points to the BRC canopy as a central player in this mechanism. We propose a model where initiation of bone remodeling coincides with the induction of proximity of the vasculature to endosteal surfaces, thereby allowing capillary‐BRC canopy interactions that activate marrow events, including recruitment of osteoblast progenitors to bone remodeling sites. © 2013 American Society for Bone and Mineral Research.